Biodegradable films incorporating Malaysian stingless bee propolis: development, characterization, and potential for food packaging - Mohd Hanapiah, Nur Ayuni; Syed Salleh, Sharifah Nur Amalina; Wan Johari, Wan Lutfi; Mohd Adzahan, Noranizan (Elsevier, 2024)
Three different Malaysian stingless bee propolis samples were examined using the ethanolic extraction method for total flavonoid (TFC) and phenolic content (TPC), antioxidant, and antibacterial activities. Additionally, the biodegradable films were developed and characterized, this study also aims to enhance the functional qualities for possible use in active food packaging by combining corn starch (CS) with propolis extract (PE). The propolis samples were extracted with 70 % ethanol and analysed through a UV–VIS spectrophotometer for determination of antioxidant, TPC, and TFC. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) was used as scavenging test for free radicals, while Folin-Ciocalteu and aluminium chloride (AlCl3) were used to measure total flavonoid and phenolic contents. The data presented in this study showed significant differences in TPC and TFC identified in each sample ranged from 31.95 to 59.48 mg/mL GAE and 53.88 to 59.49 mg/mL RE, respectively. The findings also showed significant differences in the antibacterial activities of Malaysian stingless bee propolis, especially against Gram-positive bacterial strains. In comparison to the control treatments, the ethanolic propolis extract treatments also improved the film's physiochemical and antibacterial qualities. The incorporation of PE into CS resulted in decreased moisture content of the films from 17.20 % to 14.39 %, whereas the solubility significantly decreased from 17.44 % to 12.14 %. The weight of CS and PE film lowered significantly after 14 days and the weight loss percentage also demonstrated that bioplastic degradation occurred. The propolis extract was able to prevent the growth of foodborne bacteria since the present data revealed that the microbial count was significantly lower than control groups by displaying an acceptable limit of aerobic plate count for red meat products, which is lower than 6 log CFU/g. Propolis from Malaysian stingless bees may offer a viable substitute for synthetic additives in biodegradable food packaging films. Its antimicrobial and antioxidant properties support its application for sustainable food preservation.